Удосконалення методики визначення збитків від пошкоджень в розподільних електричних мережах - Мірошник, Олександр Олександрович; Черкашина, Вероніка Вікторівна; Пазій, Володимир Григорович; Дишлевський, Андрій Володимирович (Національний технічний університет "Харківський політехнічний інститут", 2018)
Виконано аналіз методів пошуку аварійних пошкоджень в розподільних лініях з урахуванням їх структури. Запропоновано методику, яка дозволяє визначити збитки від аварійних пошкоджень.

The analysis of methods of search of accidents damages in distribution lines with the account of their structure is executed. A methodology is proposed, which allows to determine damage from accidental damage. The choice of the optimal strategy for diagnosing accidental damage depends on the structural construction of the distribution electrical grids and their technical and economic characteristics.
Improvement of methods for determining damages from damage in distribution electric networks
Keywords: пошук місця пошкодження; search for damage